Sistem Pakar Diagnosa Penyakit dan Hama Tanaman Pepaya Menggunakan Metode Forward Chaining dan Naïve Bayes - Prayoga, Aldo Rio; Wahyuddin, M. Iwan; Andrianingsih, A (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Papaya is an agricultural product that can be grown anywhere. This causes papayas to be susceptible to pests and diseases, which can cause delays in the harvest period. So we need an expert system application that can help diagnose pests and diseases in papaya so that it can make it easier for papaya plant cultivators. The research has a goal to create an expert system application that can provide information on papaya plant diseases and can make it easier to diagnose diseases that exist in papaya and can be accessed easily anywhere by the public. This system is designed using Forward Chaining and Naïvei Bayes Methods. This expert system application is expected to make it easier for users to diagnose diseases and pests on papaya plants without having to require experts directly, based on the discussion and results in this research, the accuracy value of this expert system application has an accuracy value of 95% in diagnosing diseases and pests on papaya plants.